Perguruan Tinggi: Pusat Pengembangan SDM dan Transformasi Pemahaman Ekonomi dan Perbankan Syari'ah - Amirullah, Amirullah (Universitas Brawijaya, Indonesia, 2008)
In kontek growth of global economics and free computation market competition market free, college of Islam is progressively sued by active role and its ability of goodness as agent of transformasi assess in all life segment, including economic segment, and also in yielding human resource energy which with quality. Pass Through to with refer to activity which is college diemban which is accumulation in the field of teaching and education, devotion and research at society Three Darma College, hence process off is transfer of knowledge of and transfer of of needed to value is economic expansion and banking of Syari'ah can overcome. To come to at expectations, college in course of value transformasi need strategic stages, steps, for example: first, inculcating love to knowledge and science and technology. This step can be socialized to pass hrough creation of atmosphere draw near student with life and nature and also phenomenons that happened in it. Both second, creating process and atmosphere learn to teach capable to awaken and creativity menumbuhkembangkan and innovation and also enthusiasm and spirit of learning student. Third, energy spirit fighting, excellence knowledge and professionalism as two keyword which need is continuously buzzed in the effort developing human resource which with quality is. Fourth, moral and august ethic kindness as personification of belief in God and fear at God as vital elementary value very in face of life which is global progressively.